Darier's Disease: Report of a Case with Facial Involvement - Chaninan Kositkuljorn; Poonkiat Suchonwanit (Karger Publishers, 2019)
Darier's disease is a relatively rare autosomal dominant genodermatosis with a defect in the desmosomal attachment due to a mutation in the ATP2A2 gene. The condition is characterized by multiple hyperkeratotic papules predominantly in seborrheic areas on the head, neck, and trunk, with less frequent involvement of the oral mucosa. Histopathologically, the lesions reveal suprabasal clefts in the epithelium with acantholytic and dyskeratotic cells. Facial involvement in Darier's disease is one of the common presenting features. However, it has been once reported in a severe, chronic form as leonine facies in a long-standing case. To raise awareness of facial involvement in Darier's disease, we herein report a 65-year-old female patient with prominent facial lesions.